The Relationship between Gadget Use and Elementary School Students' Psychomotor Abilities - Nugraha Ramadhan; Dinar Dinangsit; Encep Sudirjo (Universitas Negeri Semarang, 2026)
This study is based on the fact that elementary school-aged children frequently use gadgets, which can impact their motor skills and the quality of movement in daily life. The purpose of this study was to determine the relationship between electronic device use and the psychomotor abilities of first-grade elementary school students, as well as the contribution of electronic device use to psychomotor development. The study also examined the frequency of children's use of electronic devices. This may impact the balance between digital and physical activity, both of which are important components of child development. This study used a quantitative correlational approach and an ex post facto design. The study involved 60 randomly selected students from Pasir Biru and Cikeusik Elementary Schools. The TGMD2 Test of Gross Motor Development, Second Edition was used to assess students' psychomotor abilities. A questionnaire was also used to measure the level of device use. The data were then analyzed using SPSS version 25 to conduct descriptive statistical analysis, normality tests, Spearman correlation tests, and linear regression analyses. The results of the study showed a negative relationship between device use and psychomotor abilities, but this relationship was not statistically significant, with a correlation coefficient of -0.028. Furthermore, the analysis showed that the contribution of device use to psychomotor abilities was relatively low. This suggests that many other factors outside the study were more influential, such as physical activity, the play environment, and parenting styles. Therefore, it can be concluded that device use is not an important or primary factor influencing students' psychomotor abilities. Therefore, efforts to maximize students' psychomotor development should focus on increasing physical activity and controlling device use wisely and in a balanced manner in everyday life.